2005
DOI: 10.1113/jphysiol.2005.086066
|View full text |Cite
|
Sign up to set email alerts
|

Gain modulation by serotonin in pyramidal neurones of the rat prefrontal cortex

Abstract: Serotonin (5-HT) is widely implicated in brain functions and diseases. The vertebrate brain is extensively innervated by 5-HT fibres originating from the brain stem, and 5-HT axon terminals interact with other neurones in complex ways. The cellular mechanisms underlying 5-HT function in the brain are not well understood. The present study examined the effect of 5-HT on the responsiveness of neurones in the neocortex. Using patch-clamp recording in acute slices, we showed that 5-HT substantially increased the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 58 publications
5
75
0
Order By: Relevance
“…We also manipulated sAHPs via application of the serotonergic (5-HT 2 ) agonist ␣me5HT (20 M), which reduces sAHPs (Villalobos et al, 2005) and increases neuronal gain to DC stimulation (Zhang and Arsenault, 2005). We confirmed that sAHPs were significantly reduced by ␣me5HT (Ϫ0.8 Ϯ 0.2 mV, n ϭ 9; vs ACSF, Ϫ3.3 Ϯ 0.4 mV; p Ͻ 0.001, paired t test) (Fig.…”
Section: Strong Correlation Between Adaptation and Calcium-dependent supporting
confidence: 60%
“…We also manipulated sAHPs via application of the serotonergic (5-HT 2 ) agonist ␣me5HT (20 M), which reduces sAHPs (Villalobos et al, 2005) and increases neuronal gain to DC stimulation (Zhang and Arsenault, 2005). We confirmed that sAHPs were significantly reduced by ␣me5HT (Ϫ0.8 Ϯ 0.2 mV, n ϭ 9; vs ACSF, Ϫ3.3 Ϯ 0.4 mV; p Ͻ 0.001, paired t test) (Fig.…”
Section: Strong Correlation Between Adaptation and Calcium-dependent supporting
confidence: 60%
“…I sAHP is related to a variety of computational properties of neurons, including spike-frequency adaptation (Adams et al, 1982;Madison and Nicoll, 1984), gain of input-to-output transformations (Zhang and Arsenault, 2005;Thurley et al, 2008) and preference for spike-time or spike-rate coding (Prescott et al, 2006;. Despite its importance, its molecular correlates remain unidentified (Stocker, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The gain of the response function can be modulated by various mechanisms, e.g., through the action of neuromodulators (Zhang and Arsenault 2005;Thurley et al 2008), the strength of after-hyperpolarization currents (Higgs et al 2006), or a balanced change of noisy excitation and inhibition (Hô and Destexhe 2000;Destexhe et al 2001;Doiron et al 2001;Chance et al 2002;Longtin et al 2002;Mitchell and Silver 2003). These forms of gain modulation are implementable in point neurons, and were not considered here.…”
Section: Discussionmentioning
confidence: 99%